Hubungan Pengetahuan dengan Keikutsertaan Wanita Usia Subur (WUS) dalam Pemeriksaan IVA - Misrina Retnowati; Naomi Pramila (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
Cancer is a non-communicable disease that has become a health problem in the world, including in Indonesia. The high mortality rate from cervical cancer globally can be reduced by early detection through IVA testing. The high number of cervical cancer sufferers in Indonesia is due to the low motivation of WUS to perform IVA examinations, based on WUS 'knowledge of IVA examinations. This study aims to determine the relationship between knowledge and participation of women of childbearing age in IVA examinations in Pangebat Village. This type of research is an analytical survey research using a cross sectional approach. The population in this study were all women of fertile age (WUS) in Pangebat village as many as 851 people. The sample in this study as many as 90 people were taken by proportional random sampling technique. Univariate analysis using frequency distribution and bivariate analysis using Chi Square test. The results showed that knowledge of WUS about cervical cancer was mostly good as many as 48 people (53.3%) and most of them did not follow IVA examination as many as 56 people (62.2%). The results of bivariate analysis using the chi square test obtained p value = 0.010, which means that there is a relationship between knowledge and participation of WUS in the IVA examination. The conclusion is that there is a relationship between knowledge and the participation of women of childbearing age in IVA examinations in Pangebat Village.